Penerapan Persamaan Diferensial Model Eksponensial dan Logistik dalam Mengestimasi Jumlah Penduduk Di Nusa Tenggara Barat - Rida Alkausar Hardi; Ifan Hasnan Dani; Rio Satriyantara; Hady Rasikhun (Griya Journal of Mathematics Education and Application, 2026)
Rapid population growth can lead to social and economic problems if it is not properly controlled. This studyaims to model the population of West Nusa Tenggara using differential equation models, namely theexponential and logistic models. Population data were obtained from Statistics Indonesia for the period from1994 until 2024. The exponential model was applied by calculating the growth rate based on the actual data,while the suitability of the logistic model was also examined. The results indicate that the logistic model isnot valid because it produces a negative carrying capacity, which contradicts the fundamental assumptionsof the model. Meanwhile, the second exponential model, with a population growth rate of 1.5% per year,provides the best accuracy based on a Mean Absolute Percentage Error (MAPE) value of 0.78%. Therefore,the exponential model is considered the most appropriate approach for predicting the population of West NusaTenggara until 2034.